AI*IA 2011: Artificial Intelligence Around Man and Beyond XIIth International Conference of the Italian Association for Artificial Intelligence, Palermo, Italy, September 15-17, 2011. Proceedings - Pirrone, Roberto; Sorbello, Filippo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 12th International Conference of the Italian Association for Artificial Intelligence, AI*IA 2011, held in Palermo, Italy, in September 2011. The 31 revised full papers presented together with 3 invited talks and 13 posters were carefully reviewed and selected from 58 submissions. The papers are organized in topical sections on machine learning; distributed AI: robotics and MAS; theoretical issues: knowledge representation and reasoning; planning, cognitive modeling; natural language processing; and AI applications.
Keywords: Computer science; Data mining; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Mathematical Logic and Formal Languages; Computation by Abstract Devices; User Interfaces and Human Computer Interaction; Pattern Recognition